Hubungan Penggunaan Automatic Dependent Surveillance – Broadcast Dengan Keselamatan Lalu Lintas Penerbangan di Perum LPPNPI Cabang Semarang - Kalfin Saputra; Hodi Hodi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study evaluates the relationship between the Automatic Dependent Surveillance - Broadcast (ADS-B) system and safety in air traffic management at the Semarang Branch of Perum LPPNPI. The need for enhanced efficiency and operational safety in air travel has increased, particularly following the rise in aircraft movements post-COVID-19. ADS-B, a satellite-based monitoring system, provides real-time data on aircraft position, speed, and altitude to air traffic controllers, facilitating quick and accurate decision-making. Employing a quantitative associative approach, the study uses saturated sampling, including all 26 active Air Traffic Controller personnel at the Semarang Branch. Data were gathered through a Likert scale questionnaire measuring respondents' perceptions of the variables. Analysis using SPSS revealed a significance value of 0.000, indicating a statistically significant relationship between ADS-B usage and flight safety. The correlation coefficient of 0.780 demonstrates a strong positive relationship, while the determination coefficient of 0.608 indicates that 60.8% of variations in flight safety can be attributed to the ADS-B system. Additionally, the t-test results confirm that the calculated t value exceeds the t table, reinforcing the conclusion of a significant and consistent relationship between the variables.